Barriers to and facilitators of advance care planning implementation for medical staff after the COVID-19 pandemic: an overview of reviews - Yu Sun; Ryota Inokuchi; Masao Iwagami; Nanako Tamiya; Takehiro Sugiyama; Kyoko Hanari; Kensuke Shimada; Ayaka Sakamoto; Thomas Mayers (BMJ Open, 2023)
Objective The COVID-19 pandemic has impacted the capacity for advance care planning (ACP) among patients, families and healthcare teams. We sought to identify and review the barriers to and facilitators of ACP implementation for medical staff in different settings (eg, hospitals, outpatient palliative care, nursing and care homes) during the pandemic.Design This study employed an overview of reviews design. We searched the MEDLINE, CENTRAL, Web of Science and Embase databases for studies published between 8 December 2019 and 30 July 2023. We used AMSTAR 2 to assess the risk of bias.Results We included seven reviews. Common barriers to ACP implementation included visitation restrictions, limited resources and personnel and a lack of coordination among healthcare professionals. In care and nursing homes, barriers included a dearth of palliative care physicians and the psychological burden on facility staff. Using telemedicine for information sharing was a common facilitator across settings. In hospitals, facilitators included short-term training in palliative care and palliative care physicians joining the acute care team. In care and nursing homes, facilitators included ACP education and emotional support for staff.Conclusions Visitation restrictions and limited resources during the pandemic posed obstacles; however, the implementation of ACP was further hindered by insufficient staff education on ACP in hospitals and facilities, as well as a scarcity of information sharing at the community level. These pre-existing issues were magnified by the pandemic, drawing attention to their significance. Short-term staff training programmes and immediate information sharing could better enable ACP.PROSPERO registration number CRD42022351362.